The Featherweight Giant: Unraveling the Atmosphere of a 17 Myr Planet with JWST - Pa Chia Thao; Andrew W. Mann; Adina D. Feinstein; Peter Gao; Daniel Thorngren; Yoav Rotman; Luis Welbanks; Alexander Brown; Girish M. Duvvuri; Kevin France; Isabella Longo; Angeli Sandoval; et al. (The Astronomical Journal)
The characterization of young planets (<300 Myr) is pivotal for understanding planet formation and evolution. We present the 3–5 μ m transmission spectrum of the 17 Myr, Jupiter-size ( R ∼10 R _⊕ ) planet, HIP 67522b, observed with JWST NIRSpec/G395H. To check for spot contamination, we obtain a simultaneous g -band transit with the Southern Astrophysical Research Telescope. The spectrum exhibits absorption features 30%–50% deeper than the overall depth, far larger than expected from an equivalent mature planet, and suggests that HIP 67522b’s mass is <20 M _⊕ irrespective of cloud cover and stellar contamination. A Bayesian retrieval analysis returns a mass constraint of 13.8 ± 1.0 M _⊕ . This challenges the previous classification of HIP 67522b as a hot Jupiter and instead, positions it as a precursor to the more common sub-Neptunes. With a density of <0.10 g cm ^−3 , HIP 67522 b is one of the lowest-density planets known. We find strong absorption from H _2 O and CO _2 (≥7 σ ), a modest detection of CO (3.5 σ ), and weak detections of H _2 S and SO _2 (≃2 σ ). Comparisons with radiative-convective equilibrium models suggest supersolar atmospheric metallicities and solar-to-subsolar C/O ratios, with photochemistry further constraining the inferred atmospheric metallicity to 3 × 10 solar due to the amplitude of the SO _2 feature. These results point to the formation of HIP 67522b beyond the water snowline, where its envelope was polluted by icy pebbles and planetesimals. The planet is likely experiencing substantial mass loss (0.01–0.03 M _⊕ Myr ^−1 ), sufficient for envelope destruction within a gigayear. This highlights the dramatic evolution occurring within the first 100 Myr of its existence.